The Influence of Internalization of Islamic Values in Strengthening Students' Intentions to Enroll in Muhammadiyah University in DKI Jakarta - Trisamanta, Mohammad; Sihombing, Sabrina O; Meilani, Yohana F. C. P (Journal of Ecohumanism, 2024)
The study aimed to investigate Muhammadiyah High School students' intentions to enroll in Muhammadiyah University in DKI Jakarta. The research method uses an explanatory quantitative approach, with a survey design. Data collection used questionnaires to 400 students in Jakarta with convenience sampling; data analysis technique with Partial Least Square using Smart PLS. The result of the study indicates a positive influence of parental social support on attitude toward behavior. Furthermore, brand awareness and expectations had a positive influence on attitudes toward behavior. Attitudes toward behavior had a positive influence on intentions to enroll, as well as subjective norms and perceived behavioral control. However, attitudes toward behavior, subjective norms, and perceived behavioral control did not have a positive influence on intentions to enroll when reinforced by the internalization of Islamic values. Attitudes toward behavior served as a mediator in the positive influence of parental social support, brand awareness, and expectations on intentions to enroll. Attitudes toward behavior also mediated the positive influence of parental social support, brand awareness, and expectations on intentions to enroll, strengthened by internalization of Islamic values.